2008
DOI: 10.1002/dvg.20387
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal lethality and cardiovascular defects in CXCR7‐deficient mice

Abstract: CXCR7 is a G-protein coupled receptor that was recently deorphanized and shown to have SDF1 and I-TAC as high affinity ligands. Here we describe the characterization of CXCR7-deficient mice that were generated to further investigate the function of this receptor in vivo. Expression analysis using a LacZ reporter knockin revealed that postnatally Cxcr7 was specifically expressed in cardiomyocytes, vascular endothelial cells of the lung and heart, the cerebral cortex and in osteocytes of the bone. Adult tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
125
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 38 publications
(67 reference statements)
6
125
0
Order By: Relevance
“…Thus, CXCR7 could be envisaged as a marker for B cells exiting the GC and possibly of extrafollicular plasmablasts. Such role for CXCR7 as marker for GC egress would have been difficult to observe in mice with targeted deletion of CXCR7, because the animals were reported to die at birth and therefore immune responses could not be studied [36,55]. A possible mechanism for CXCR7-dependent modulation of CXCR4 function could be receptor heterodimerization [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CXCR7 could be envisaged as a marker for B cells exiting the GC and possibly of extrafollicular plasmablasts. Such role for CXCR7 as marker for GC egress would have been difficult to observe in mice with targeted deletion of CXCR7, because the animals were reported to die at birth and therefore immune responses could not be studied [36,55]. A possible mechanism for CXCR7-dependent modulation of CXCR4 function could be receptor heterodimerization [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Although expression patterns for this receptor remain controversial (8,9,13,25,26), there is general agreement that it can be expressed on the membranes of endothelial cells and smooth muscle cells in various tissues (9,16,20,27). The ligands for CXCR7 are CXCL11 and SDF-1 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies suggest that CXCR7 is a nonsignaling, decoy receptor that scavenges and degrades chemokine ligands (28,29). However, although there is evidence to suggest that CXCR7 does not signal through classical G-protein-mediated pathways (14,28), many studies have demonstrated an important role of this receptor in physiological and pathological processes (9,25,(30)(31)(32). CXCR7-deficient mice were shown to die within the first week after birth due to cardiovascular malformations (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting evidence has revealed that CXCR7 is involved in tumorigenesis (Maksym et al, 2009). CXCR7 knockout mice have demonstrated cardiac valve malformation or enlarged hearts (Leung et al, 2007;Gerrits et al, 2008), and no brain defects were observed in these animals. CXCR7 mRNA expression was considerably increased in the granular layer and in the CA3 pyramidal cell layer in the postnatal rat brain (Schönemeier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%